2023
DOI: 10.1007/s10340-023-01678-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ecology of triatomines: current knowledge and implications for Chagas disease vector management

David Alavez-Rosas,
Reyna Vargas-Abasolo,
Claudia I. Albores-Flores
et al.

Abstract: Triatomines (Hemiptera: Heteroptera: Reduviidae), commonly known as conenose or kissing bugs, includes species of outstanding medical importance given their role as vectors of the protozoan parasite Trypanosoma cruzi Chagas (Kinetoplastida: Trypanosomatidae), the aetiological agent of Chagas disease. Herein, we present an updated review of the chemical ecology of triatomines, with special reference to molecules involved in the communication of these insects. Infochemicals, including hormones and semiochemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…Trypanosoma cruzi can also affect sexual dimorphism, due to hormones that may serve as communication signals (Alavez-Rosas et al, 2023) as reported by May-Concha et al (2021), who studied the infection of T. cruzi in Triatoma dimidiata Latreille (Hemiptera: Reduviidae: Triatominae), and when measuring the antennae sensilla, they reported that infected insects have a greater perception of contact stimuli and olfactory perception than uninfected insects, which favors vectorial transmission of the parasite.…”
Section: Introductionmentioning
confidence: 85%
“…Trypanosoma cruzi can also affect sexual dimorphism, due to hormones that may serve as communication signals (Alavez-Rosas et al, 2023) as reported by May-Concha et al (2021), who studied the infection of T. cruzi in Triatoma dimidiata Latreille (Hemiptera: Reduviidae: Triatominae), and when measuring the antennae sensilla, they reported that infected insects have a greater perception of contact stimuli and olfactory perception than uninfected insects, which favors vectorial transmission of the parasite.…”
Section: Introductionmentioning
confidence: 85%